Simplifying
18x + -44 = 13y + -38
Reorder the terms:
-44 + 18x = 13y + -38
Reorder the terms:
-44 + 18x = -38 + 13y
Solving
-44 + 18x = -38 + 13y
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '44' to each side of the equation.
-44 + 44 + 18x = -38 + 44 + 13y
Combine like terms: -44 + 44 = 0
0 + 18x = -38 + 44 + 13y
18x = -38 + 44 + 13y
Combine like terms: -38 + 44 = 6
18x = 6 + 13y
Divide each side by '18'.
x = 0.3333333333 + 0.7222222222y
Simplifying
x = 0.3333333333 + 0.7222222222y
Answer: First solve the parentheses using order of operations. Then add and subtract from left to right.
Demo:
(3 * 11) = 33
Equation now looks like:
63 - 21 + 33
63 - 21 = 42
Equation now looks like:
42 + 33
42 + 33 = 75
The value of this expression is 75.
It should be B If I am correct if I am not I am sorry
Step-by-step explanation:
here's the answer to your question